N170 wave amplitude analysis on driving performance on highway road - Mohamed Aminuddin, Mai Mariam; Mohd Nasir, Haslinah; Mustaffa, Izadora; Brahin, Noor Mohd Ariff (Penerbit Universiti, UTeM, 2018)
Attention in the physiological definition is taking possession of the mind in one of several simultaneously events of thoughts which implies withdrawing some things to deal effectively with other. In driving particularly, attention is essential to keep track of the driver’s vigilance to avoid the road accident. In this paper, analysis of the driver’s attention is done through their driving performance from both of Electroencephalographic (EEG) amplitude and accident score. During the driving experiment, two stimulations will be given to the subjects which are silent environment (in certain dB) and listening to the live streaming radio. The results show that when listening to the radio, the driving performance is improved and the score of the accident is reduced as well. This figure gave a concrete justification that driver’s attention able to maintain or even increase when the stimulation is triggered.